The spread characteristics of music videos relating to COVID-19 in China online video platforms - Jiangnan Zhao; Cheng Chen; Lai Zhao (Association for Scientific Computing Electrical and Engineering (ASCEE), 2020)
This paper aims to explaining how was the behavior of music videos in China and online video platforms during the outbreak of COVID-19, which is related to the situation of COVID-19, were taken as the research object. Firstly, the data were collected and proceeded, then the time distribution, the types of the author, geographical distribution, theme, the types of music were gathered for data statistics. Secondly, this study analyzed the characteristics of the production and spread of these music videos, which were displayed visually. This research is library research. The author conducted in-depth studies related to various literacies that explain the objects and subjects of this study. Finally, this paper systematically analyzed the effect and influence of social literature and art in a public event.